Aus Büchern Bücher machen Zur Produktion und Multiplikation von Wissen in frühneuzeitlichen Kompilationen - Zweifel, Simone (Cultures and Practices of Knowledge in History, 2021)
Be it angels, meteorites, or harps - there is a wealth of knowledge in the more than one-hundred publications that, by the mid-eighteenth century, had appeared in four languages under the name of Johann Jacob Wecker (1528-1586/88). Broad networks were created in order to collect and disseminate this knowledge. The practice of compilation formed the basis of this so far largely overlooked, successful production of books.